The Muslim prayer encyclopedia - "Maqsood, Ruqaiyyan Waris" (Goodword Press New Delhi, 1998)
The Muslim Prayer Encyclopaedia by Ruqaiyyah Waris could be greatly enriched by including explanations of abstract, spiritual concepts related to prayer, helping readers grasp the deeper, more personal aspects of Islamic worship.